UmiLiciouss Enterprise / Muhammad Haziq Hazwan Musa - Musa, Muhammad Haziq Hazwan (2019)
Assalamualaikum W.B.T, my pleasure to say thank you so much to my beloved and kind hearted lecture for ENT530 Madam Zanariah Binti Zainal Abidin for guided me along this way to complete my social media portfolio. Thank you to my parents for supporting me like gave morale, ideas, and motivation to run this business managerially. Thank you also to my friends around me that give morale support that helped me finished the work ' and used time wisely. I also want to thank to every single person who helped me directly or indirectly for my social media portfolio. I may could not complete my work without their helped. I would like to express my gratitude to everybody for their advices and guidance along this way until I finished my work. I apologize to all unnamed persons who helped me in various ways to complete this portfolio and I hope this social media business can give me and others a little bit of knowledge about Entrepreneurship field. I ended my word with a lot of thank you.